PROTOTIPE PEMESANAN BAHAN PUSTAKA MELALUI WEB MENGGUNAKAN ACTIVE SERVER PAGE (ASP) - Setiabudi, Djoni Haryadi; Setiawan, Ishak (Institute of Research and Community Outreach - Petra Christian University, 2002)
Electronic commerce is one of the components in the internet that growing fast in the world. In this research, it is developed the prototype for library service that offers library collection ordering especially books and articles through World Wide Web. In order to get an interaction between seller and buyer, there is an urgency to develop a dynamic web, which needs the technology and software. One of the programming languages is called Active Server Pages (ASP) and it is combining with database system to store data. The other component as an interface between application and database is ActiveX Data Objects (ADO). ASP has an advantage in the scripting method and it is easy to make the configuration with database. This application consists of two major parts those are administrator and user. This prototype has the facilities for editing, searching and looking through ordering information online. Users can also do downloading process for searching and ordering articles. Paying method in this e-commerce system is quite essential because in Indonesia not everybody has a credit card. As a solution to this situation, this prototype has a form for user who does not have credit card. If the bill has been paid, he can do the transaction online. In this case, one of the ASP advantages will be used. This is called